Sharp bound for the ergodic maximal operator associated to Cesàro bounded operators - Cabral, Enrique Adrian (2018)
We consider positive invertible Lamperti operators Tf(x)=h(x)Φf(x) such that Φ has no periodic part. Let An,T be the sequence of averages of T and MT the ergodic maximal operator. It is obvious that if MT is bounded on some Lp, 1